Polyols in grape berry: transport and metabolic adjustments as a physiological strategy for water-deficit stress tolerance in grapevine - Conde, Artur (2015)
Polyols are important metabolites that often function as carbon and energy sources and/or osmoprotective solutes in some plants. In grapevine, and in the grape berry in particular, the molecular aspects of polyol transport and metabolism and their physiological relevance are virtually unknown to date. Here, the biochemical function of a grapevine fruit mesocarp polyol transporter (VvPLT1) was characterized after its heterologous expression in yeast. This H+-dependent plasma membrane carrier transports mannitol (K-m=5.4 mM) and sorbitol (K-m=9.5 mM) over a broad range of polyols and monosaccharides. Water-deficit stress triggered an increase in the expression of VvPLT1 at the fully mature stage, allowing increased polyol uptake into pulp cells. Plant polyol dehydrogenases are oxireductases that reversibly oxidize polyols into monosaccharides. Mannitol catabolism in grape cells (K-m=30.1 mM mannitol) and mature berry mesocarps (K-m=79 mM) was, like sorbitol dehydrogenase activity, strongly inhibited (50-75%) by water-deficit stress. Simultaneously, fructose reduction into polyols via mannitol and sorbitol dehydrogenases was stimulated, contributing to their higher intracellular concentrations in water-deficit stress. Accordingly, the concentrations of mannitol, sorbitol, galactinol, myo-inositol, and dulcitol were significantly higher in berry mesocarps from water-deficit-stressed Tempranillo grapevines. Metabolomic profiling of the berry pulp by GC-TOF-MS also revealed many other changes in its composition induced by water deficit. The impact of polyols on grape berry composition and plant response to water deficit stress, via modifications in polyol transport and metabolism, was analysed by integrating metabolomics with transcriptional analysis and biochemical approaches.